Současné tetování z hlediska „rituálního“ jednání - Alena Kajanová; Klára Jersáková; Michal Růžička (AntropoWebzin, 2012)
Tattooing is one of the most widely spread forms of body modification in contemporary Czech society. The goal of this article is to inquire into contemporary practices of tattooing with regard to their “ritual” functions. Our research question was whether ritual functions attached to tattooing still remain, or whether they have already been entirely substituted by purely aesthetic functions. We were further interested in the motivations leading to the decision of getting a tattoo and their relation to certain time periods, such as crises. Is obtaining a tattoo a response to a crisis, or rather to the fact that it has been overcome? Our sample consists of sixteen respondents wearing at least two tattoos. The respondent’s narrations are supplemented by the perspectives of professional tattoo artists. Our data analysis suggests that among both the tattooed and tattoo artists, tattoo art is perceived rather in its aesthetic and individualizing functions than in its social-ritual function. For the tattooed themselves, tattooing carries deep meanings attached to the process of their (social) individualization. They perceive the very process of tattooing, accompanied by considerable pain, as a form of individualized rite of passage. For some of the tattooed, the new tattoo concludes a previous period of life, while opening a new one, into which they emerge as new beings.